BUSANA TRADISIONAL TARI RANGGUK DI KECAMATAN KUMUN DEBAI KOTA SUNGAI PENUH - Fenti Vidia (Institut Seni Indonesia Padangpanjang, 2022)
Rangguk dance is an art originating from the Kumun Debai sub-district of Sungai Penuh city which is performed at traditional events such as Kenduri Sko and welcoming regional guests. The clothes worn at the Rangguk Dance are in the form of brackets, skirts from songket fabric along with complements and other accessories. Rangguk dance is performed by women both married and unmarried with a total of 7 to 11 dancers. In 2018 Rangguk Dance has been designated as Indonesia's Intangible Cultural Heritage by the Directorate of Cultural Heritage and Diplomacy. A dance cannot be separated from clothing that can show the characteristics of the dance. Rangguk Dance fashion has a special meaning in the disclosure of the messages to be conveyed through the clothing. This study aims to describe the meaning and symbols contained in rangguk dance clothing.